2020
DOI: 10.1101/2020.01.20.909259
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ultrasound imaging links soleus muscle neuromechanics and energetics during human walking with elastic ankle exoskeletons

Abstract: 26Unpowered exoskeletons with springs in parallel to human plantar flexor muscle-tendons can reduce the 27 metabolic cost of walking. We used ultrasound imaging to look 'under the skin' and measure how 28 exoskeleton stiffness alters soleus muscle contractile dynamics and shapes the user's metabolic rate 29 during walking. Eleven participants (4F, 7M; age: 27.7 ± 3.3 years) walked on a treadmill at 1.25 m s -1 30 and 0% grade with elastic ankle exoskeletons (rotational stiffness: 0-250 Nm rad -1 ) in one tr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 89 publications
0
51
0
Order By: Relevance
“…Using . We used the rate of the metric of interest (average per second) for a more apt comparison to metabolic rate (J s -1 ) (See [43] for a similar approach).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using . We used the rate of the metric of interest (average per second) for a more apt comparison to metabolic rate (J s -1 ) (See [43] for a similar approach).…”
Section: Discussionmentioning
confidence: 99%
“…When exoskeleton assistance is applied, biological moment and thus muscle-tendon force decreases, while strain on the tendon decreases. Modeling and experimental studies of hopping [45,48,59] and walking [43,47,50] with ankle exoskeletons suggest that muscle lengths are in fact longer and undergo increased excursion with increased exoskeleton assistance, and this could limit muscle force capacity and metabolic economy. As well, the biological system may be resistant to increased muscle strain to avoid injury and compensations may arise to limit range of motion [60][61][62].…”
Section: -4)mentioning
confidence: 99%
“…The improvement of the walking economy could thus be bene cial for both healthy individuals and those with reduced mobility [2]. Many attempts have been made to assist walking especially unpowered assistive devices have demonstrated the capacity to capture and release energy throughout the gait cycle, and have shown the ability to achieve a net reduction in energy consumption [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the power for walk is mainly provided by the positive work of the ankle and hip [12]. The greatest portion of energy waste occurs in muscles such as soleus muscle and gastrocnemius muscle during the push-off phase of the walking cycle [4,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Moderating optimal values, found from modeling analyses for the developed 636 assistive devices was found in other studies. For example, in a recent study, Nucklos et 637 al., showed that the optimal ankle stiffness from the assistive device should not be more 638 than (around) 50% of the quasi stiffness of the ankle joint [77] which could be found by 639 neuromuscular models. 640 3) Feedback signal: The last novelty of this study is introducing the ground 641 reaction force (GRF) as a useful feedback signal.…”
mentioning
confidence: 99%